Start Up India: An Exploration of Youth Technology based Entrepreneur Opportunities in Rural Area - Tak, Sana (International Journal of Computer Sciences and Engineering, 2025)
The goals of a startup are to be the boss himself and create work for others, which guarantee a lot of resistance and sacrifice. A large population with a high percentage of middle income groups, educated young people with technical training, IT proficiency, high internet and mobile penetration are some of the drivers that have offered the opportunity to spread the startup revolution in India. "Make-in-India" initiatives and other government programs have also pressed new companies with many people who have come into play. Starting a business is a well planned and disciplined exercise with due consideration of internal and external factors that can affect the sustainability of the company. The idea behind the company, the size of the market, the objectives of income and profit are some of the important factors that must be clearly defined before embarking on the journey. Time, teamwork and tenacity are important elements that determine business success. Businesses and entrepreneurship are the drivers of economic growth in rural areas of India. With the current challenges faced by traditional rural sectors, the future success of the rural economy is inextricably linked to the ability of rural entrepreneurs to innovate and identify new business opportunities that create jobs and income in rural areas. A rural entrepreneur faces many problems due to the lack of availability of the main services in the rural areas of developing countries like India. Lack of education, financial problems, insufficient technical and conceptual capacity is too difficult for rural entrepreneurs to create industries in rural areas. This paper seeks to discover the challenges and skills for the potential of rural entrepreneurship and their prospects of being a successful entrepreneur.